Etika Bisnis Lembaga Keuangan Syariah - Saiful Bahri (LPPM ISNJ Bengkalis, 2012)
As known that sharia financial institutions growth in this latest period, shown better works as well as performances. About asset, funding and financing indicated that sharia financial institution as positively subscribed by Moslems hopes. As well as sharia compliance based institution, it is an obligation to be good business. Because in the several theory mentioned those good ethics meant good business. Then meant also ethics was most important for many industries included to sharia financial institution. By the qualitative method, this study to try to point out and describe structures of business ethics in Islam and to implicate to sharia financial institution operation.